A case study on Batik Malaysia Berhad - Abdul Jamil, Nordin (2000)
The Case study on Batik Malaysia Berhad (BATIK) is written in two parts as follows: PART I – Case Description PART II – Case Analysis BATIK, a subsidiary of MARA Holdings Sdn Bhd (MHSB) was incorporated in 1974. The main core activities of the company are batik retailing, wholesaling, exporting, and sales of raw materials. Batik retailing is done through direct selling to retailers and individuals and also sold through outlets at various locations especially in the Klang Valley. The company’s performance in the past years and up to the present times had not been encouraging. It’s bottom line for all the past years had been in the red. It will take a long time before the accounts can be in the black again. It has problems in all its functional areas. All these are symptoms to the problems. The actual problem is still on the management of the company. The CEO of the company has been changed at the rate of every two or three years. The question is, was the company’s problems due to the incompetence of the past CEOs, or was it due to other reasons? The case has been analyzed in all possible angles taking into considerations the various fields of studies, such as marketing, finance, strategic management, etc. in order to arrive at the proposed recommendations. As for this case, the propose recommendations for implementation can be summarized as follows: a. Finance Capital injection should be made by the parent company to BATIK. b. Marketing BATIK should concentrate on its domestic trade. This can be done through extensive promotion, appointment of agents/ salesmen who will then concentrate on aggressive marketing, and by opening additional outlets at strategic locations in the country to serve the tourist and the locals. c. Administration BATIK is to hire a professional Chief Executive Officer (CEO), so that the company can be managed in a more professional manner. BATIK should also give priority on the training of the company staff. The future of BATIK will depend on what direction MHSB has for the company and the plans and strategies that her top management has and how he/she is going to implement them.